A novel transcript, VNN1‐AB, as a biomarker for colorectal cancer. Issue 9 (29th March 2014) - Løvf, Marthe; Nome, Torfinn; Bruun, Jarle; Eknæs, Mette; Bakken, Anne C.; Mpindi, John P.; Kilpinen, Sami; Rognum, Torleiv O.; Nesbakken, Arild; Kallioniemi, Olli; Lothe, Ragnhild A.; Skotheim, Rolf I.
<x xml:space="preserve">Abstract</x> Colorectal cancer is a global health challenge with high incidence rate and mortality. The patients' prognosis is strongly associated with disease stage and currently there is a need for improved prognostic and predictive biomarkers. In this study, novel colorectal cancer‐specific transcript structures were nominated from whole transcriptome sequencing of seven colorectal cancer cell lines, two primary colorectal carcinomas with corresponding normal colonic mucosa and 16 normal tissues. The nominated transcripts were combined with gene level outlier expression analyses in a cohort of 505 colorectal cancers to identify biomarkers with capacity to stratify colorectal cancer subgroups. The transcriptome sequencing data and outlier expression analysis revealed 11 novel colorectal cancer‐specific exon–exon junctions, of which 3 were located in the gene VNN1. The junctions within VNN1 were further characterized using rapid amplification of cDNA ends (RACE) and the prevalence of the subsequently characterized novel transcript, VNN1‐AB, was investigated by real‐time RT‐PCR in 291 samples of miscellaneous origins. VNN1‐AB was not present in any of the 43 normal colorectal tissue samples investigated, but in 5 of the 6 polyps, and 102 of the 136 (75%) colorectal cancers. We have identified a novel transcript of the VNN1 gene, with an organ‐confined complete specificity for colorectal neoplasia.